Semantic Web for Reliable Citation Analysis in Scholarly Publishing. - Tous, Ruben; Guerrero, Manel; Delgado, Jaime (Information Technology & Libraries, 2011)
Analysis of the impact of scholarly artifacts is constrained by current unreliable practices in cross-referencing, citation discovering, and citation indexing and analysis, which have not kept pace with the technological advances that are occurring in several areas like knowledge management and security. Because citation analysis has become the primary component in scholarly impact factor calculation, and considering the relevance of this metric within both the scholarly publishing value chain and (especially important) the professional curriculum evaluation of scholarly professionals, we defend that current practices need to be revised. This paper describes a reference architecture that aims to provide openness and reliability to the citation-tracking lifecycle. The solution relies on the use of digitally signed semantic metadata in the different stages of the scholarly publishing workflow in such a manner that authors, publishers, repositories, and citation-analysis systems will have access to independent reliable evidences that are resistant to forgery, impersonation, and repudiation. As far as we know, this is the first paper to combine Semantic Web technologies and public-key cryptography to achieve reliable citation analysis in scholarly publishing.